Perpajakan Optimal dalam Perspektif Hukum Pajak Berfalsafah Pancasila - Johan, Arvie; Hikmah, Fadhilatul; Anditya, Anugrah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 3 (2019)DO - 10.24843/JMHU.2019.v08.i03.p03, 2019)
Pancasila as philosofiche grondslag guides positioning tax law in Indonesia. While taxation as a science has developed from the ability to pay's principle towards the optimal taxation concept .  There are two main objectives in this research such as identifying the characteristics of tax law based on the Pancasila philosophy and describing tax law based on the Pancasila philosophy in the context of optimal taxation. To answer both questions, normative research method was utilized by identifying the Pancasila philosophy of tax law and the concepts and principles of tax law and optimal taxation. This research reveals two things: firstly, the characteristics of tax law based on the Pancasila Philosophy include tax compliance, welfare, and burden prevention. Secondly, optimal taxation is compatible with the last two aspects of tax law based on Pancasila Philosophy. Yet, we found conflicting concept between tax compliance based on Pancasila philosophy and horizontal equity as part of optimal taxation. The object of conflict is a progressive tariff tax. Pancasila sebagai philosofiche grondslag memberikan pegangan mengenai pemosisian hukum pajak di Indonesia. Sementara perpajakan sebagai suatu disiplin keilmuan telah berkembang dari prinsip kemampuan bayar menuju konsep perpajakan yang optimal. Ada dua tujuan artikel penelitian ini yakni mengidentifikasi karakteristik hukum pajak berfalsafah Pancasila, serta menjelaskan hukum pajak berfalsafah Pancasila dalam konteks perpajakan optimalPenelitian ini menggunakan metode normatif melalui identifikasi pajak berfalsafah Pancasila, serta identifikasi konsep dan asas-asas hukum pajak dan pajak optimal. Hasil temuan penelitian terdiri atas 2 hal, yaitu pertama, karakteristik hukum pajak berfalsafah Pancasila meliputi kepatuhan pajak, kesejahteraan, dan pencegahan beban. Kedua, perpajakan optimal sesuai dengan dua aspek terakhir dari hukum pajak berfalsafah Pancasila. Namun, terdapat ketidakcocokan diantara kepatuhan pajak berdasarkan Pancasila dengan keadilan horizontal berdasarkan konsep perpajakan optimal. Objek konflik yang dimaksud adalah tarif pajak progresif.